Design of a pierce oscillator for CMOS SAW resonator - Karim, Jamilah; Nordin, Anis Nurashikin; Alam, A. H. M. Zahirul (2012)
Development of microelectromechanical system (MEMS) based oscillators have drawn significant attention because it provides CMOS compatibility and multifrequency operations on a single chip. Recently, integrated MEMS resonators have shown great performance by attaining high quality factors and high frequency operations of up to the GHz range. Of interest, is fully integrated SAW resonator which can be connected to an oscillator circuit on the same chip. For oscillator circuit simulations, the CMOS SAW resonator was modeled using its RLC equivalent circuits. The insertion loss of CMOS SAW resonator used in this design is 35.8dB, with motional resistance Rx=8.95kΩ and the motional capacitance and inductance are Cx=199aF and Lx=350uH. For a MEMS resonator to be able to function as an oscillator it needs to be coupled with supporting circuits. There are various types of supporting oscillator circuit topologies namely the pierce oscillator, differential amplifier oscillator or the transimpedance amplifier circuit topology. The topology to be chosen depends on the design requirement, the loop gain of 1 and the zero phase shifts. For this work, the pierce circuit topology was chosen due to its simplicity and high frequency stability. This simple circuit comprising of 4 transistors, helps to achieve low power consumption and excellent phase noise characteristics. This paper will present the analysis, design and the simulation result of a high gain (>; 36dB) and low power pierce circuit topology for MEMS CMOS SAW resonator. The circuit was designed in 0.18um CMOS technology and yield open loop gain >; 36dB.